2008
DOI: 10.1270/jsbbs.58.461
|View full text |Cite
|
Sign up to set email alerts
|

Development of a routine procedure for single nucleotide polymorphism marker design based on the Tm-shift genotyping method

Abstract: To establish a routine procedure for SNP marker development, the previously reported T m -shift SNP genotyping procedure was validated and extensively improved. The effect of introducing mismatched nucleotides into allele-specific primers, using alternative fluorescent dyes, and varying the DNA polymerase species on SNP discrimination was examined at more than 100 known SNP loci in a solanaceous crop, eggplant. As a result, it has been shown that a success rate over 80% can be achieved with T m -shift SNP geno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 12 publications
(9 reference statements)
1
6
0
Order By: Relevance
“…Furthermore, the growth of P. vulgaris was decreased with the increase in sewage sludge concentration from 60% to 100%. The findings were also supported by Fukuoka et al (2010) who reported that the growth of eggplant was decreased due to the application of more concentration of sewage effluent. (Khan et al, 2007;Kumar & Chopra, 2012).…”
Section: Effect Of Sewage Sludge On Vegetative Growth Of S Melongenasupporting
confidence: 70%
See 2 more Smart Citations
“…Furthermore, the growth of P. vulgaris was decreased with the increase in sewage sludge concentration from 60% to 100%. The findings were also supported by Fukuoka et al (2010) who reported that the growth of eggplant was decreased due to the application of more concentration of sewage effluent. (Khan et al, 2007;Kumar & Chopra, 2012).…”
Section: Effect Of Sewage Sludge On Vegetative Growth Of S Melongenasupporting
confidence: 70%
“…Eggplant (Solanum melongena L.) is identified as one of the most valuable vegetable packed with essential nutrients (Fukuoka et al, 2010;Dar et al, 2014). The eggplant is a delicate, tropical perennial often cultivated as a tender or half-hardy annual in temperate climates (Nunome et al, 2001;Hirakawa et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sequence data were processed using the phred/ phrap/cross_match package (Ewing et al 1998). SNPs found between parental lines of mapping populations were mainly genotyped using the melting temperature (T m )-shift PCR method , with some modifications (Fukuoka et al 2008). When reliable allele specificity could not be achieved using T m -shift PCR, such SNPs were genotyped by direct sequencing using the same primer sets used for SNP discovery.…”
Section: Snp and Indel Discovery Marker Development And Genotypingmentioning
confidence: 99%
“…All SNPs markers developed by Fukuoka et al (submitted), total of 630 markers, were screened for detecting polymorphisms among parents of ALF2/NAF2 populations (ESM_1). To genotype these SNPs, we used the Tm-shift genotyping method originally reported by Wang et al (2005) and partially modified by Fukuoka et al (2008) to improve detection efficiency. We genotyped 135 ALF2 and 93 NAF2 F 2 plants with the markers.…”
Section: Snp Analysismentioning
confidence: 99%